Using switchable solvent as a solvent and catalyst for in situ transesterification of spent coffee grounds for biodiesel synthesis. (October 2019) - Nguyen, Hoang Chinh; Nguyen, My Linh; Wang, Fu-Ming; Liang, Shih-Hsiang; Bui, Thi Loan; Ha, Hoang Hieu; Su, Chia-Hung
Graphical abstract: Highlights: An in situ transesterification of SCG using DBU as a solvent and catalyst was built. DBU-catalyzed in situ transesterification of SCG is a green production process. Within a short reaction time, a SCG biodiesel yield of 96.13% was achieved. DBU was effective for reuse in in situ transesterification of SCG. Abstract: This study developed a novel in situ transesterification process by combining the solvent and catalyst functions of 1, 8-diazabicyclo[5.4.0]undec-7-ene (DBU) for biodiesel synthesis from spent coffee grounds (SCG). The influence of reaction parameters on the reaction was investigated. The maximum biodiesel yield of 96.13% was observed at DBU-to-SCG and methanol-to-SCG ratios of 20 and 10 mL/g, respectively; a reaction temperature of 130 °C; and a reaction time of 60 min. Notably, the polarity of DBU could be reversibly regulated, thus facilitating excellent product separation. Moreover, DBU could be effectively reused for 10 cycles to yield high biodiesel conversion. DBU-catalyzed in situ transesterification of SCG is a promising, ecofriendly, and economically viable biodiesel production process.